An Analysis of the Implementation of the Problem-Based Learning (PBL) Model to Strengthen Students' Disciplinary Character in Pancasila Education: Evidence from SD Negeri Bibisluhur 1 Surakarta, Academic Year 2025/2026 - Prima Novianingrum; Anita Trisiana; Muhammad Faruq Hanafi (Madako Elementary School, 2026)
The low discipline of students in doing and collecting assignments and the dominance of learning that is still oriented towards the delivery of material causes the strengthening of the character of discipline has not developed optimally in Pancasila Education learning. This study aims to analyze the application of the PBL model in strengthening the disciplinary character of grade IV students of SD Negeri Bibisluhur 1 Surakarta for the 2025/2026 Academic Year. The research uses a descriptive qualitative approach supported by descriptive quantitative data. The research subjects consist of teachers and students of grade IV. Data is collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions with data validity using triangulation of sources and techniques. The PBL syntax was carried out very well at the stage of problem orientation (91.40%), student organization (89.75%), investigation (92.60%), presentation of results (90.85%), and evaluation (93.20%). The implementation of PBL contributes to strengthening compliance with rules, responsibilities, active discussion, and timeliness in completing and collecting tasks.  These findings show that PBL has the potential to be an effective pedagogical strategy to integrate active learning with the strengthening of students' disciplinary character in a sustainable manner.